2016
DOI: 10.1007/s40194-016-0316-x
|View full text |Cite
|
Sign up to set email alerts
|

Crack propagation analysis and rehabilitation by HFMI of pre-fatigued welded structures

Abstract: This paper deals with a crack propagation analysis of welded structures and rehabilitation after pre-fatigue loading by the high-frequency mechanical impact (HFMI) posttreatment technique. The investigated specimen type is a thinwalled longitudinal stiffener made of mild steel S355. Fracture mechanical calculations are primarily performed on the basis of the weight-function approach. Thereby, the local residual stress condition at the weld toe is considered by the aid of a structural weld simulation, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
2
28
0
3
Order By: Relevance
“…All fatigue test data points are above the IIW recommendation, even if a bonus factor of 1.5 for HFMI treatment and a benign thinness bonus factor are applied [10]. Leitner et al [11] found that the influence and effective of stress ratio may be related to the fundamental change in the local residual stress state. HFMI-treated high-strength steel joints it is observed that the effect of the HFMI-induced compressive residual stress state acts as significant benefit factor to increase the fatigue resistance due to this post-treatment technique and leads to a reduction of the local residual stress condition.…”
Section: Introductionmentioning
confidence: 95%
“…All fatigue test data points are above the IIW recommendation, even if a bonus factor of 1.5 for HFMI treatment and a benign thinness bonus factor are applied [10]. Leitner et al [11] found that the influence and effective of stress ratio may be related to the fundamental change in the local residual stress state. HFMI-treated high-strength steel joints it is observed that the effect of the HFMI-induced compressive residual stress state acts as significant benefit factor to increase the fatigue resistance due to this post-treatment technique and leads to a reduction of the local residual stress condition.…”
Section: Introductionmentioning
confidence: 95%
“…A number of different methods exist for monitoring crack propagation. For welded structures, local strain measurement at hot spots [21,22] is widely used due to its flexibility and easy handling. This procedure is expedient if the specimen has a low number of distinct hot spots, such as a longitudinal stiffener, where crack initiation will occur.…”
Section: Detection Of the Crack Initiation Pointmentioning
confidence: 99%
“…They concluded that the butt joint treated with HFP achieved fatigue life almost similar to the fatigue strength of base metal, the T-joint Transition knee point Nk shifts to a lower number of load cycles implying a significant increase in endurable strength limit, while the longitudinal attachment HFP treated shows an increase of the slope k in the low-cycle fatigue regime. The data of these investigations are shown in Martin Leitner et al [17] also investigated the crack propagation of the welded structure of the carbon steel S355 and rehabilitate its using post treatment HFMI. Around 1 mm pre-crack was occurred on the welded T joint of the carbon steel S355 before post treated with HFMI/PIT.…”
Section: Fig 12: Nominal S/n-curves For Variable Amplitude Block Loamentioning
confidence: 99%